Knowledge of radiation exposure in common radiological investigations: a comparison between radiologists and non-radiologists. Issue 4 (25th August 2011) - Lee, Ryan K L; Chu, Winnie C W; Graham, Colin A; Rainer, Timothy H; Ahuja, Anil T
Abstract : Background: Radiological examinations are commonly requested for patients to aid clinical diagnosis. However, many doctors do not realise how much radiation dosage their patients are exposed to during radiological investigations. This study aims to assess and compare the knowledge of radiologists and non-radiologists about radiation doses of common radiological investigations. Methods: A prospective questionnaire study of doctors about the dosage of commonly performed radiological investigations in a university teaching hospital in Hong Kong. Participants were asked to indicate the average dose of radiation (in mSv) for a standard chest x-ray exposure. Doctors were then asked to estimate the doses of radiation (measured in chest x-ray equivalents) for various radiological procedures. The results of radiologists and non-radiologists were compared. Results: 158 doctors (25 radiologists and 133 non-radiologists) completed the questionnaire. The overall accuracy was 40% for radiologists and 16% for non-radiologists. One-third of non-radiologists could not distinguish radiological examinations with or without ionising radiation. No non-radiologists correctly stated the radiation dose (in mSv) of a conventional chest x-ray, and 77% underestimated the dose of radiological examinations. For radiologists, only 32% were correct for the radiation dose of a conventional chest x-ray while 7% underestimated the radiation doses. Conclusion: Knowledge of radiation doses of investigation is generally inadequate among radiologists, and particularly poor in non-radiologists. Underestimation of radiation doses may expose patients to increasing radiological investigation and exposure to radiation hazards. Awareness of the radiation hazard of radiological examinations should be raised among medical professionals.